(3OQQ GdHMGQ aj TQM GdCTYGQs - (3CMeO Hf eMehO Hf eMeOs
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje GdMeO dbOje dGjWhQ afGA jbhd HYO MeO Gddg GdCMO CMeO Hf eMehO Hf eMeO WGdeG cfJ ai WdH JaSjQ eYJed ehLR GddaX cKjQ GdeYfi s
(3BNQgG (B:s
(3hai GdeJf HWf NHJ hgj GdCQV GdeWeFf hCfUJhG CUZhG bGd GdEeGe Ydjce CeQ SjOce hGdMeO ddg QH GdYGdejf s
(3GdfSNI HgG MhGTs
(3cJHJ HYV GdcdeGJ HGdMeQIs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
Keywords: (3GdJaSjQ hYdhe GdbQBfs